PENINGKATAN KEMAMPUAN MEMBACA HURUF VOKAL PADA PESERTA DIDIK SEKOLAH DASAR KELAS RENDAH MELALUI MEDIA BIGBOOK DI SD MUHAMMADIYAH 1 KREMBUNG: - Vina Aruni Lathifah; Ahmad Nurefendi Fradana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve reading skills in lower grades by using learning media in the learning and teaching process of students. With this learning media, students are motivated and interested in studying the learning taught by educators in the classroom, the media used is bigbook media. bigbooks allow students to learn to read by remembering by repeating readings. So that through bigbooks, students' reading skills are expected to increase. This is because bigbooks are made with attractive pictures and colors that have been adjusted to the characteristics of the reading and the characteristics of the students, this can improve reading skills where this ability is a basic ability that must be possessed by students who will continue to be used at the next grade level, this study chose one of the materials in the Indonesian language subject to be combined with bigbook learning media, namely recognizing vowels. Introduction to vowels and consonants must be introduced first by students in the first grade of elementary school. Vowels are letters that symbolize vowels in Indonesian consisting of five letters, namely a, i, u, e, o. This study uses data collection techniques with observation sheets and learning outcomes. By using the PTK research method, it can improve the reading ability of lower grade students, especially grade 1 (one) by using bigbook teaching media and get the results of this increase of 32.84%. This can overcome learning problems, especially in learning.